Analisis Putusan Nomor 2058 K/Pdt/2019 tentang Wanprestasi Perjanjian Jual Beli Rumah - Emir Syarif Fatahillah Pakpahan; Nofrianti Limbong; Citra Bunga Ramahdita (CV Rewang Rencang, 2025)
Analysis of the Supreme Court Decision Number 2058 K/PDT/2019 regarding breach of contract for house sale and purchase. This decision emphasizes the importance of fulfilling obligations in house sale and purchase agreements. This analysis discusses the legal basis, case facts, and implications of the decision on the parties involved. The results of the analysis show that the decision meets the relevant legal basis and has significant implications in the context of law and society.